STUDY OF CELLULOSE-BASED FABRICS TREATED WITH MODIFIED AEROSIL-380 NANOPARTICLES - Khallieva Salima Mammatrasurovna; Norova Rukhsora Nematovna (Web of Journals Publishing, 2025)
The article studies 4 different types of cellulose-based fabrics treated with modified aerosil-380 nanoparticles. The initial state of the treated fabric samples and their state after aqueous treatment were microscopically examined. The results of the studies showed that the flame-retardant properties of the fabrics treated with aqueous treatment in accordance with the requirements of regulatory documents were preserved.